Dialog dan Tindakan Kolektif Kelompok Tani dalam Program Sertifikasi Kakao di Provinsi Sulawesi Barat - Nur Asia; Sarwititi Sarwoprasodjo; Dyah Gandasari (Jurnal Komunikasi Pembangunan, 2018)
The cocoa certification program is the implementation of cocoa management practices that meet sustainable agricultural standards. This program is part of the commitment of cocoa sector stakeholders to realize sustainable cocoa. West Sulawesi Province is one of cocoa production centers in Indonesia. The implementation of cocoa certification in this province is still low, about 8.4% of the total cocoa farmers. This study aims to determine the potential for sustainability of the adoption of Cocoa Certification from development communication aspect by conducting an assessment on dialogue and collective action of farmer groups. The research conducted in Luyo Sub-District Polewali Mandar District West Sulawesi Province using survey method with descriptive correlation analysis. The sample size is 41 groups with 205 respondents. Descriptive analysis shows the average index of the implementation of community dialogue and collective action of 56.05,50,88 and 65.72 from a maximum score of 100. The results indicated that perception of farmers on the observability of Cocoa Certification and the role of facilitators are significant related to dialogue and collective action of farmer groups. The dialogue in the group is significant correlated with their collective action. So, some farmer groups have potential to continue to adopt the Cocoa Certification standard but others have potential to quit.